In her boots - Dell'Antonia, K. J. (G.P. Putnam's Sons, 2022)
"From the New York Times bestselling author of The Chicken Sisters comes a delightfully entertaining story about a ruse that goes awry and a chaotic homecoming that proves that confronting your past can sometimes set you free"--